انڈین مسلم پرسنل لاءاورہندوستانی مسلمانوں پر اس کےاثرات؛ ایک تجزیاتی مطالعہ: An analytical study of Indian Muslim Personal Law & its impact on Indian Muslims - Ur Rahman , Dr. Sami; Ahmad, Dr. Khalil; Dr. Khalid Mahmood, Dr. Khalid Mahmood (Al-Amīr Research Journal for Islamic Studies, 2024)
This article offers a detailed examination of "Contemporary Aspects of Muslim Personal Law in India," tracing its historical roots and evaluating its relevance in the modern context. It begins with an introduction to Muslim Personal Law (MPL), providing a historical overview of its presence and application throughout India's pre-colonial and colonial eras. The discussion highlights how MPL has been a fundamental aspect of the socio-legal landscape for Indian Muslims, adapting over centuries to the changing political and cultural environments. The article then addresses the establishment of the All India Muslim Personal Law Board (AIMPLB) in 1973, exploring its objectives and its pivotal role in overseeing the application of MPL within the Indian judiciary and Muslim community. It discusses the board's mission to ensure that MPL adheres to the Qur’anic doctrines and Hadith, while also navigating the challenges posed by contemporary legal and social frameworks. Additionally, the role of AIMPLB in the broader context of global Islam is considered, with a focus on how the board mediates between traditional Islamic law and modernity to address new social realities. This includes debates on gender rights, marriage, divorce, and inheritance, reflecting the board's ongoing struggle to reconcile religious directives with progressive societal norms. The article further delves into current discussions surrounding MPL, such as its interaction with secular laws and its impact on the multicultural fabric of Indian society. It explores how increased awareness and education among Indian Muslims, particularly women, are prompting calls for reforms that align MPL more closely with universal human rights standards while retaining its religious essence. In conclusion, the article provides a nuanced analysis of MPL's role in contemporary India, illustrating its dynamic nature as it continues to evolve in response to both internal community needs and external societal changes. By doing so, the article sheds light on the intricate balance between tradition and modernity within the framework of Muslim Personal Law. Keywords: Muslim Personal Law, All India Muslim Personal Law Board, Sharia Law Adaptation, Contemporary Islamic Issues, Religious Law and Secularism, Indian Muslims.